Layanan Bimbingan dan Konseling di SMK Negeri 1 Lalan - Lestari, Novi; Yosef, Yosef; Oktarina, Santi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2020)
Guidance and counseling help students / counselees to understand, accept, direct, make decisions, and realize their decisions responsibly. In an effort to realize integrated guidance and counseling services, strong support is needed. This study aims to determine the implementation of the guidance and counseling service curriculum in SMK Negeri 1 Lalan. This study used the method of observation. The results of this study indicate that the implementation of the implementation of counseling services at SMK Negeri 1 Lalan is not yet ideal based on the applicable curriculum Guidance and counseling programs provide services that are integrated withdevelopment programs for all aspects of life for students/counselors at school. Guidance and counseling at SMKN 1 Lalan strived to identify the needs of the personal, social, learning, and career fields.